Improving Traffic Management and Pedestrian Safety in Urban Bangladesh: Insights from Rangpur City Corporation - Tamrin, Samantha (ABC Journal of Advanced Research, 2024)
Rapid urbanization has led to various problems in Bangladesh, especially in urban areas like Rangpur, where traffic management and pedestrian safety have become significant challenges. This study intends to explore the current stage of traffic management and pedestrian safety in Rangpur City and to bring out some suggestions for improvement. A mixed method approach was employed to gather data by integrating a quantitative survey with 200 pedestrians and a qualitative Key Informant Interview with 10 academicians, government officials, and urban planning experts. Descriptive analysis for the quantitative data and thematic analysis for the qualitative data were carried out to analyze the collected data. The results indicate significant deficiencies in pedestrian infrastructure, for example, bad sidewalk conditions, absence of pedestrian crossings, and very low presence of traffic police during peak hours. Furthermore, low public awareness of pedestrian safety was found to be a significant factor in worsening pedestrians' risks. The study suggests a wide range of infrastructural development, such as well-constructed roads, foot over bridges, and a higher number of traffic police on the streets, in addition to public awareness campaigns and stricter enforcement of traffic laws. Implementing the suggested measures could significantly improve pedestrians' safety and traffic management in Rangpur, leading to a safer urban environment per global safety standards.